COVID-19 teleassistance and teleconsultation: a matched case-control study (MIRATO project, Lombardy, Italy) - Bernocchi, Palmira; Crotti, Giacomo; Beato, Elvira; Bonometti, Francesco; Giudici, Vittorio; Bertolaia, Patrizia; Perger, Elisa; Remuzzi, Andrea; Bachetti, Tiziana; La Rovere, Maria Teresa; Dalla Vecchia, Laura Adelaide; Angeli, Fabio; et al. (Frontiers in Cardiovascular Medicine, 2023)
Background. During the COVID-19 pandemic, telemedicine has been recognised as a powerful modality to shorten the length of hospital stay and to free up beds for sicker patients. Lombardy, and in particular the areas of Bergamo, Brescia, and Milan, was one of the regions in Europe most hit by the COVID-19 pandemic. The primary aim of the MIRATO project was to compare the incidence of severe events (hospital readmissions and mortality) in the first three months after discharge between COVID-19 patients followed by a Home-Based Teleassistance and Teleconsultation (HBTT group) program and those discharged home without Telemedicine support (non-HBTT group). Methods. The study was designed as a matched case-control study. The non-HBTT patients were matched with the HBTT patients for sex, age, presence of COVID-19 pneumonia and number of comorbidities. After discharge, the HBTT group underwent a telecare nursing and specialist teleconsultation program at home for three months, including monitoring of vital signs and symptoms. Further, in this group we analysed clinical data, patients’ satisfaction with the program, and quality of life. Results. Four hundred twenty-two patients per group were identified for comparison. The median age in both groups was 70±11 years (62% males). One or more comorbidities were present in 86% of the HBTT patients and 89% in the non-HBTT group (p=ns). The total number of severe events was 17 (14 hospitalizations and 3 deaths) in the HBTT group and 40 (26 hospitalizations and 16 deaths) in the non-HBTT group (p=0.0007). The risk of hospital readmission or death after hospital discharge was significantly lower in HBTT patients (Log-rank Test P=0.0002). In the HBTT group, during the 3-month follow-up, 5355 teleassistance contacts (13±4 per patient) were performed. The number of patients with one or more symptoms declined significantly: from 338 (78%) to 183 (45%) (p<0.00001). Both the physical (PCS12: 5.9±11.4) component and the mental (MCS12: 4.4±12.7) component of SF-12 improved significantly (p<0.0001). Patient satisfaction was very high in all participants. Conclusions. Compared to usual care, an HBTT program can reduce severe events (hospital admissions/mortality) at 3-month from discharge and improve symptoms and quality of life. Clinical trial registration: [www.ClinicalTrials.gov, NCT04898179].